Curriculum Model of Typography for Undergraduate Student by Using New Media: A Comparative Study - Mohamad Shahrizan Mohamad Sidik (Advances in Humanities and Contemporary Studies, 2023)
In Malaysia, the higher education institutions, IPTA and IPTS, that offer the curriculum of typography for undergraduate students in the graphic design department, are still practicing the method of teaching in a conventional way rather than in a modern way. Studies are focusing on the curriculum of typography, where the educators still use the conventional method of teaching to deliver the lectures rather than using the modern method of teaching in classrooms. Students will become bored if the educator uses the same method of imparting knowledge that was used twenty years ago. They are all born into a technological world that teaches them the quickest and most effective way to learn. The purpose of this study is to design and develop a new style of teaching the curriculum of typography using new media elements as a way to deliver knowledge to students in higher education. Using a qualitative research method, followed by a comparative study, the study will compare the best online learning for typography education that uses new media tools as a teaching method. The final stage is the development and design of a new curriculum model for typography using new media elements. Evaluation results showed all participants strongly agreed that this new method helped students be fast learners in the content of typography education. Sharing and managing curriculum content via online learning (E-Learning) can advance the knowledge by demonstrating a positive outcome, as demonstrated by the prototype test. This study on the curriculum model using new media gives a new perspective, showing that students at this stage really understand the content of the electronic learning and give good responses by answering all the questions, with the majority of participants giving a good response to the online courses.